1999
DOI: 10.1038/sj.bjc.6690580
|View full text |Cite
|
Sign up to set email alerts
|

Detection of regional melanoma metastases by ultrasound B-scan, cytology or tyrosinase RT-PCR of fine-needle aspirates

Abstract: Summary Physical examination and ultrasound B-scan screening are important follow-up procedures in melanoma patients with regional disease. However, they do not allow definite diagnosis of suspicious lesions. Fine-needle aspiration cytology (FNAC) enhances the diagnostic accuracy in such patients but, unfortunately, reaches its technical limits, particularly when very small or necrotic lesions are examined. We therefore tested whether tyrosinase reverse transcription polymerase chain reaction (RT-PCR) of fine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 20 publications
0
8
1
2
Order By: Relevance
“…It is interesting to note that the dark colour of the aspirate almost constantly correlates with a cytological diagnosis of melanoma metastasis, which contains large amounts of melanin. Our experience leads us to state, in contrast with other authors [8], that rapidity, high level of sensitivity, low cost and absence of side effects make FNA the procedure of choice to achieve a definitive diagnosis, even in small lesions.…”
Section: Discussionecontrasting
confidence: 54%
See 1 more Smart Citation
“…It is interesting to note that the dark colour of the aspirate almost constantly correlates with a cytological diagnosis of melanoma metastasis, which contains large amounts of melanin. Our experience leads us to state, in contrast with other authors [8], that rapidity, high level of sensitivity, low cost and absence of side effects make FNA the procedure of choice to achieve a definitive diagnosis, even in small lesions.…”
Section: Discussionecontrasting
confidence: 54%
“…In accordo con la nostra esperienza, malgrado l'opinione di altri autori [8], la rapidità dell'esecuzione della FNA, la sua alta sensibilità, il basso costo e l'assenza di effetti collaterali la rende procedura di scelta al fine di porre certa diagnosi anche nelle piccole lesioni.…”
Section: Piccoleunclassified
“…Examination procedures were regarded to be negative if no suspicion of metastatic disease was raised. In case of detection of any suspicious lesion, definitive diagnosis was obtained by fine-needle aspiration cytology 21, 22 and by subsequent histopathologic examination of surgically removed lesions.…”
Section: Patient Selection and Stagingmentioning
confidence: 99%
“…In particular, HSP-70 expression is believed to be of value in the identification of melanoma patients with poor prognosis (Kalogeraki et al, 2006). Studies also have shown tyrosinase reverse transcription polymerase chain reaction (RT-PCR) on fine-needle aspirates (FNA-PCR) to increase the diagnostic sensitivity of cytology, when US/ FNAC fails to detect the sentinel node metastasis in melanoma (Voit et al, 1999). Such studies have been performed on exfoliative samples as well.…”
Section: Further Advances In Cytology Of Melanomamentioning
confidence: 99%
“…More recently, lymph node ultrasound (US) with fine needle aspiration cytology (FNAC) is considered a potential cost effective alternative for an SLNB (Voit et al, 2006;van Akkooi et al, 2010). Although, rare studies have reported very low sensitivity which is attributed to tiny and necrotic lesions (Voit et al, 1999;van Rijk et al, 2006); most authors have emphasized the importance of USguided FNAC in the detection of sentinel lymph node metastasis (Voit et al, 1999(Voit et al, , 2002(Voit et al, , 2006. With a positive cytology of the sentinel node, surgeons can proceed with the direct radical lymph node dissection in patients with melanoma.…”
mentioning
confidence: 99%